Evaluation of alkali residue-stabilized soil in road construction with optimization of mechanical properties and environmental risk assessment - Jing Hua; Wenyi Xie; Guangxia Liu; Qun Li; Yan Zhou; Ruijie Che; Fenghe Wang; Xiaowei Xu; Chang Liu (PLoS ONE, 2026)
The effective utilization of alkali residue (AR) is a central issue and an urgent challenge for the green transformation of the soda ash industry. While research has primarily focused on the mechanical performance of AR-based materials, their long-term environmental risks, particularly under dynamic conditions, have been relatively overlooked. This study evaluates AR-stabilized soil for road construction by simultaneously optimizing its mechanical properties and conducting a comprehensive environmental risk assessment for shallow groundwater contamination. Through laboratory tests, we identified the AR substitution rate that maximizes the California Bearing Ratio (CBR) and water stability. To address the limitations of traditional static leaching tests, we integrated material degradation and contaminant transport models to dynamically simulate pollutant release and migration under realistic, non-steady conditions. Our findings reveal that an AR substitution rate between 10% and 50% yields optimal mechanical performance. However, environmental risk analysis indicates a significant increase in risk beyond 35%, with manganese (Mn) and nickel (Ni) exposure concentrations potentially exceeding Class III groundwater quality standards. Sensitivity analysis confirms the AR substitution rate as the most critical factor influencing environmental risk. Therefore, we recommend strictly controlling the AR substitution rate to ≤35% in road construction, providing a science-based, dual-criteria (mechanical and environmental) guideline for the safe and sustainable utilization of industrial waste in geotechnical engineering.